2013
DOI: 10.2460/ajvr.74.3.481
|View full text |Cite
|
Sign up to set email alerts
|

Effect of transportation during periods of high ambient temperature on physiologic and behavioral indices of beef heifers

Abstract: Results indicated transportation during periods of high ambient temperatures caused transient changes in physiologic and behavioral indices of beef heifers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(52 citation statements)
references
References 39 publications
5
39
0
6
Order By: Relevance
“…The present study supports the results of a recently reported 46% SP increase following 4 h of transportation (Theurer et al, 2013). Although an inverse linear relationship of MEL and SP has been recently reported in a dehorning study , MEL administration did not reduce SP in the present study.…”
Section: Substance Psupporting
confidence: 93%
See 2 more Smart Citations
“…The present study supports the results of a recently reported 46% SP increase following 4 h of transportation (Theurer et al, 2013). Although an inverse linear relationship of MEL and SP has been recently reported in a dehorning study , MEL administration did not reduce SP in the present study.…”
Section: Substance Psupporting
confidence: 93%
“…Bannikov et al (2007) reported that neutrophil MMP-9 is covalently complexed with neutrophil synthesized Hp suggesting that this is a potentially useful biomarker indicating activation and degranulation of neutrophils (Theurer et al, 2013). Increases in plasma Hp-MMP-9 concentration over time are consistent with other studies reporting significantly elevated plasma Hp-MMP-9 concentrations in cattle with acute inflammation (Bannikov et al, 2011).…”
Section: Haptoglobin-matrix Metalloproteinase-9 Complexessupporting
confidence: 76%
See 1 more Smart Citation
“…Liquid chromatography-tandem mass spectrometry SP [1][2][3][4][5][6][7][8][9][10][11] Parent substance P molecule composed of 11 amino acids SP [3][4][5][6][7][8][9][10][11] Metabolite of substance P composed of the last 9 C-terminal amino acids SP [7][8][9][10][11] Metabolite of substance P composed of the last 5 C-terminal amino acids been evaluated as a response variable that may be more specific for the measurement of pain in animals. [3][4][5][6][7][8][9][10] Substance P is a biologically active peptide that has a role in neural transmission of nociceptive signals from peripheral sites to the CNS.…”
Section: Kiu Kallikrein Inhibitor Units Lc-ms-msmentioning
confidence: 99%
“…Objective, continuous behavioral monitoring using accelerometers and pedometers has been used to assess cattle behavior in a variety of scenarios. [3][4][5][6][7][8][9] Monitoring cattle location within a defined environment has also been used in an effort to identify and monitor potential behavioral changes. 8,10 The objective of this review is to describe potential benefits and challenges of remotely monitoring cattle behavior with available methodologies including clinical illness scores, visual monitoring, accelerometers, pedometers, feed intake and behavioral monitoring, global position systems, and real time location systems.…”
Section: Introductionmentioning
confidence: 99%